Physical Inactivity Is Associated With Post-discharge Mortality and Re-hospitalization Risk Among Swedish Heart Failure Patients—The HARVEST-Malmö Study - Zaghi, Amir; Holm, Hannes; Korduner, Johan; Dieden, Anna; Molvin, John; Bachus, Erasmus; Jujic, Amra; Magnusson, Martin (Frontiers in Cardiovascular Medicine, 2022)
Background Several studies have examined the role of physical activity as a predictor of heart failure (HF) mortality and morbidity. Here, we aimed to evaluate the role of self-reported physical activity as an independent risk factor of post-discharge mortality and re-hospitalization in patients hospitalized for HF, as well as study the association between physical activity and 92 plasma proteins associated with cardiovascular disease (CVD). Methods Four-hundred-and-thirty-four patients hospitalized for HF (mean age 75 years; 32% women) were screened for physical activity derived from questionnaires in the Swedish national public health survey. The median follow-up time to death and re-hospitalization was 835 (interquartile range, 390-1432) and 157 (43-583) days, respectively. Associations between baseline reported physical activity, mortality and re-hospitalization risk were analyzed using multivariable Cox regression analysis. Plasma samples from 295 study participants were analyzed with a proximity extension assay consisting of 92 proteins. Associations between proteins and physical activity were explored using a false discovery rate of <5%, and significant associations were taken forward to multivariate analyses. Results In the multivariate Cox regression model, physical inactivity, defined as physical activity time less than 1 h throughout the week was associated with increased risk of all-cause mortality (HR 1.71; CI95% 1.26-2.31; p=5.9x10-4) as well as all-cause re-hospitalization (HR 1.27; CI95% 1.01-1.60; p=0.038). Further, physical inactivity was associated with elevated plasma levels of Metalloproteinase inhibitor 4, Soluble interleukin 1 receptor-like 1, Elafin and Transferrin receptor protein 1, which are implicated in myocardial fibrosis, migration and apoptosis. Conclusions Self-reported low weekly physical activity is associated with increased risk of mortality and re- hospitalization in patients hospitalized for HF independent of traditional risk factors. Furthermore, physical inactivity was associated with elevated levels of 4 proteins linked to cardiovascular disease.